Nouns and noun phrase structure in Nubri - Dhakal, Dubi Nanda (Gipan, 2019)
This paper is a preliminary investigation of the nominal morphology and noun phrase structures of Nubri, a Tibetan variety spoken in the northern Gorkha. Nubri shares a number of inflectional and derivational features with Tibetan languages, such as Kyirong Tibetan. Like its close Tibetan varieties, a number of modifiers such as, genitive-marked nouns, demonstratives, relative clauses etc. precede the head nouns, whereas some other modifiers, such as article, emphatic marker, numerals etc. follow them in the noun phrase.